Expanding the Entrepreneurial Value Creation Model of Mishra & Zachary (2014) - My, Phuong Tran Thi; Anh, Tu Phan (Archives of Business Research, 2021)
There have been many theories applied to explain entrepreneurship and its factors. A majority have not explained an entrepreneurial process entirely. This paper builds on existing theoretical and empirical studies to detail and expand the Entrepreneurial Value Creation Model to provide a complete theoretical model of the entrepreneurship process for empirical studies in the future. Three main contributions of the research include: (1) a detailed entrepreneurial value creation model; (2) a review of 8 types of research related to Entrepreneurial Value Creation theory; and (3) seven factors influencing entrepreneurial intention and five factors influencing opportunity recognition added to the model.